"English for International Economics: A Comprehensive Course on Global Trade and Finance" - Велущак (Yuriy Fedkovych Chernivtsi National University Department of Foreign Languages for the Humanities, 2025)
The textbook enhances English language proficiency through a structured exploration of international economic principles. Each unit systematically presents core economic concepts alongside targeted vocabulary and communication activities.Real-world case studies and applied examples facilitate the practical understanding of global trade and financial systems.
In an increasingly interconnected world, the study of international economics has become essential for anyone aiming to understand the complexities of global trade, financial systems, and the economic policies that shape nations and businesses. Whether you’re pursuing a career in economics, business, finance, or trade, having a strong grasp of the key concepts in international economics is crucial to success. English for International Economics: A Guide to Global Trade and Finance was created to bridge the gap between the specialized language of economics and the practical skills needed for effective communication in the global marketplace. This textbook is specifically designed for students of international economics who wish to improve their English proficiency in the context of this field. Each chapter is focused on key topics of international economics, such as trade theory, exchange rates, financial flows, and the functioning of international financial markets. The book provides clear explanations of economic concepts, while also offering targeted language exercises to help students understand and apply the terminology used in professional settings. The content is organized into practical units, each exploring a different aspect of international economics. The first section of the book introduces the foundational concepts of international trade and the global economic system. Later chapters delve deeper into complex subjects such as tariff regulations, financial markets, currency exchange, and the roles of global financial centers. Students will find that the book not only explains the theory behind these concepts but also provides opportunities to engage with real-world examples of economic trends and challenges. The language used in this book is adapted to the needs of non-native English speakers, ensuring that key economic terms and concepts are explained in an accessible and clear manner. Additionally, each unit includes relevant case studies and examples that showcase the practical application of economic theory in global markets. These real-life examples are designed to make the material more relatable and help students to develop critical thinking skills as they analyze international economic issues. By the end of the book, students will have acquired a comprehensive understanding of the language of international economics and the key concepts that drive global trade and finance. They will be prepared to engage confidently in discussions, presentations, and written work related to international economics, and will be equipped to contribute meaningfully to the global business environment. Whether you are a student of economics, business, this book will provide you with the tools you need to navigate the world of international economics in both English and economic terms. I hope this textbook serves as a valuable resource in your academic journey and as you move into the professional world of international economics.
Keywords: international economics, finance, trade, global trade and finance